Partnership Strategy in Developing Education Quality In Islamic Based Schools - Inayah, Inayah; Kusumaningsih, Widya; Nurkolis, Nurkolis (Sekolah Tinggi Agam Islam Sumatera Medan, 2025)
This study was motivated by the importance of school partnerships with external parties as a strategy for improving the quality of education, particularly in Islamic schools that uphold the values of ukhuwah and cooperation. The objective is to describe the planning, implementation, and evaluation processes of partnerships aimed at supporting holistic educational quality improvement, encompassing academic, moral, and spiritual aspects. A descriptive qualitative approach was employed. Data were collected through interviews, observations, and documentation. Data analysis followed the Miles and Huberman model. The results of the study indicate that schools implement partnerships systematically: planning includes setting objectives, identifying programs, drafting cooperation agreements, and socialization; implementation involves various partners in the areas of health, safety, academics, and Islamic character building; evaluation is carried out through evaluation planning, monitoring obstacles, drafting recommendations, and preparing reports. However, documentation of evaluation results still needs to be improved. This study concludes that structured partnerships, aligned with the principles of mutual cooperation and Islamic values, and evaluated on a regular basis, can serve as an effective strategy to enhance the quality of Islamic education and are worthy of replication while considering local contexts.